Influenza virus ribonucleoprotein complexes gain preferential access to cellular export machinery through chromatin targeting. - Geoffrey P Chase (Public Library of Science (PLoS), 2011)
In contrast to most RNA viruses, influenza viruses replicate their genome in the nucleus of infected cells. As a result, newly-synthesized vRNA genomes, in the form of viral ribonucleoprotein complexes (vRNPs), must be exported to the cytoplasm for productive infection. To characterize the composition of vRNP export complexes and their interplay with the nucleus of infected cells, we affinity-purified tagged vRNPs from biochemically fractionated infected nuclei. After treatment of infected cells with leptomycin B, a potent inhibitor of Crm1-mediated export, we isolated vRNP export complexes which, unexpectedly, were tethered to the host-cell chromatin with very high affinity. At late time points of infection, the cellular export receptor Crm1 also accumulated at the same regions of the chromatin as vRNPs, which led to a decrease in the export of other nuclear Crm1 substrates from the nucleus. Interestingly, chromatin targeting of vRNP export complexes brought them into association with Rcc1, the Ran guanine exchange factor responsible for generating RanGTP and driving Crm1-dependent nuclear export. Thus, influenza viruses gain preferential access to newly-generated host cell export machinery by targeting vRNP export complexes at the sites of Ran regeneration.